2017
DOI: 10.1097/pcc.0000000000001329
|View full text |Cite
|
Sign up to set email alerts
|

Early Exercise in Critically Ill Youth and Children, a Preliminary Evaluation: The wEECYCLE Pilot Trial*

Abstract: Early mobilization is safe and feasible in the PICU. In-bed cycling may facilitate greater duration and intensity of mobilization, in critically ill children. A full-scale randomized controlled trial is warranted to evaluate the efficacy of this intervention on PICU-acquired morbidities and functional outcomes in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 40 publications
4
44
0
6
Order By: Relevance
“…35 The results of this review suggest that levels of comfort with mobilization may be evolving with increasing safety and feasibility data in children and indirect evidence from the adult population. Cardiorespiratory instability 20,21 Mortality (no. of deaths recorded) 1220 (9 observational studies) ⊕○○○ Very low †, ‡, § Across 9 studies, 4 deaths were reported among 494 children receiving mobilization (0.8%) vs 27 of 720 (3.75%) in control group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…35 The results of this review suggest that levels of comfort with mobilization may be evolving with increasing safety and feasibility data in children and indirect evidence from the adult population. Cardiorespiratory instability 20,21 Mortality (no. of deaths recorded) 1220 (9 observational studies) ⊕○○○ Very low †, ‡, § Across 9 studies, 4 deaths were reported among 494 children receiving mobilization (0.8%) vs 27 of 720 (3.75%) in control group.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30] Length of stay in PICU (days recorded) 30 (1 RCT) ⊕⊕○○ Low* Authors reported an overall length of PICU stay of 8.0 days (IQR, 5.0-13.8) with no distinction among groups. 20 Length of stay in PICU (days recorded) 1171 (7 observational studies) ⊕○○○ Very low †, ‡, § Two studies (n = 257 patients) did not detect a significant difference between groups. 25,26 Three studies 27,28,30 with 314 patients favor the mobility group; while one multicenter study 29 with 600 patients observed a difference favoring the group without mobilization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations